Effects of Video-Taped Instructional Strategy and Retention of Senior Secondary 2 Chemistry Students in Lagos State - C. Job, Gabriel; Opeyemi, Akinboboye (International Journal of Research in STEM Education, 2019)
This research investigated the effects of video-taped instructional strategy on the academic achievement and retention of senior secondary 2(SS2) chemistry students in lagos state. The continuous decimal academic achievement of students in this core science subject has been of major concern to stake holders in the education industry in lagos state in particular. The study adopted an experimental design of pretest – posttest factorial design. The population for this study was made up of the 4500 chemistry students in Ikorodu and Kosofe LGAs, while the sample comprised 93 SS2 chemistry students gotten through multi staged method. The instrument used was Chemistry Achievement Test (CAT). The instrument was validated by experts in Educational Technology and Measurement and Evaluation while the reliability was derived through a test – retest method. Pearson product moment correlation coefficient ® was used to arrive at 0.78. Mean and standard deviation were used to answer the research questions, which indicated that students achieved better when taught with video-taped than conventional methods. On the other hand, t-test was used to analyze the hypothesis, which indicated significant difference between students taught with video-taped and conventional method, amongst others. And it was recommended that video-taped instructional strategies by used regularly in senior secondary schools in Lagos state amongst others.